Evaluating and designing procedures in safety critical environments: a framework and taxonomy based on a critical review and synthesis. (4th July 2019) - Surabattula, Deepti; Landry, Steven J.; Caldwell, Barrett S.
Abstract: Past research in procedure following has primarily concentrated on the effect of procedure-related factors on procedure compliance and non-compliance. Non-compliance is generally considered to be uniformly negative, rather than the outcome that results from other factors. However, there is a general consensus that procedures are not designed for all situations, and that non-compliance can improve outcomes under certain situations. It is therefore important to understand procedure following based on outcomes and not only procedure compliance or non-compliance. To that end, a framework and taxonomy for understanding procedure following has been developed that enables researchers to focus on the outcome of following procedures, not simply on compliance and non-compliance.